PENGARUH KUALITAS JASA PELAYANAN JASA KESEHATAN TERHADAP KEPUASAN PASIEN PADA INSTALASI RAWAT INAP BED AH UNIT PERAWATAN BEDAH I RSU. Dr. SOETOMO SURABAYA - ., Poerwanto; ., Tunayah (Journal of Management and Business, 2006)
Within providing the good service to patients (customers) it need to be noted the determinant criteria of the treatment service quality involving the doctors' treatment, the nurses' care, the administration officers' service and the room facilities. The Hospital must considers the quick and appropriate reception procedures, has a friendly attitude to the patients, be perceptive to explain the complaints of the patients and at once quickly giving the examination, medication and treatment so that the patients feel to be responded.Based on the above explanation, the writer was attracted to choose the title: The Effect of Health Service Quality to the Patients Satisfactions at the Surgical In-Patient Installation of the Surgical Treatment Unit I of the Dr. Soetomo General Hospital of Surabaya.The analysis was used was Multiple Linear Regression Coefficient, Correlation Coefficient, Multiple Determination Coefficient (RJ, F test and t test. According to the testing results using the F test it could be concluded that the doctors' treatment (XJ, the nurses' care (XJ, the administration officers' service (XJ and the room facilities (XJ variables simultaneously had the significant effect to the patients' satisfaction (Y) at the Surgical In-Patient Installation of the Surgical Treatment Unit I of the Dr. Soetomo General Hospital of Surabaya. From the results oft test it could be concluded that the doctors' treatment (XJ, the nurses' care (XJ, the administration officers' service (XJ and the room facilities (XJ partially had the significant effects to the satisfaction of the patients (Y) at the Surgical In-Patient Installation of the Surgical Treatment Unit I of the Dr. Soetomo General Hospital of Surabaya. From result of the partial correlation test it could be concluded that there was a significant relation between the doctors' treatment (XJ, the nurses' care (XJ, the administration officers' service (XJ and the room facilities (XJ partially and the satisfaction of the patients (Y) at Surgical In-Patient Installation of the Surgical Treatment Unit I of the Dr. Soetomo General Hospital of Surabaya